P396 OUR CERTIFIED SYNCOPE UNIT EXPERIENCE; FROM DIAGNOSTIC APPROPRIATENESS TO DEVICE IMPLANTS, FROM PATIENT EDUCATION TO THE IMPACT OF THE COVID–19 PANDEMIC. REPORT ON TWO "DIFFICULT" YEARS. (18th May 2022) - Scapinelli, M; Boccedi, M; Guerra, A; Caputi, A; Merighi, S; Bagni, E
Abstract: Syncope is a frequent medical problem with an incidence of about 6.2/1000 people/year, with important impact on the patients quality of life and often difficult to diagnose and manage; in this regard, the Syncope Units certified by the Italian Group for the study of syncope were created. The following describes our experience over the last 30 months characterized by significant difficulties due to the COVID–19 pandemic. Our Syncope Unit, included in the OU of Cardiology, includes 3 doctors, 3 cardiology technicians, 2 nurses; the activity is three times a week in terms of clinic and HUTT (Head up tilt test). In 2019, 54 HUTTs were performed on patients with an average age of 67 years 50% male, with indication of vasovagal syncope (VVS) for 78% of cases, presyncope and other indications for the remaining 21%, requested by other services. The HUTT was positive for cardioinhibitory and sinus–carotid syncope with indication for Pacemaker implantation (with closed loop stimulation algorithm – CLS) for 22% of cases. In 12% of patients, an ECG–Loop recorder (ILR) was indicated, but 42% of these refused this procedure. In 2020, 32 HUTTs were performed, the same average age, with 86% indication of VVS syncope. The indication for a pacemaker implant was 15% as well as for an ILR implant. 33 to 38% of patients were educated, providing dedicated material, on the prevention of syncope. About 4% of patients refused to undergo the HUTT after the explanation of its performing modalities. The first 6 months of 2021 showed a similar trend to that of 2019. The data show a good appropriateness of the indications to the HUTT and a subsequent PM implantation rate similar to the data available in the literature. The device with CLS has shown benefits in reducing syncopal recurrences at 6 months by over 25%; only 3% of the ILRs were followed by PM implantation. The HUTT, despite of low sensitivity and specificity, is confirmed as a valid VVS characterization tool but sometimes the patient frightened by its performing methods. The COVID–19 pandemic significantly impacted our activity, related to the outpatient in office activities stop and to the shift of operators in COVID areas. We had a 40% reduction in visits and HUTTs performed with consequent missed and/or delayed diagnoses.